2008
DOI: 10.1124/jpet.107.135632
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac Attenuates the Regional Effect of λ-Carrageenan on Blood-Brain Barrier Function and Cytoarchitecture

Abstract: The microenvironment of the brain requires tight regulation for proper neuronal function. Protecting the central nervous system (CNS) from the varying concentrations of ions, proteins, and toxins in the periphery is the dynamically regulated blood-brain barrier (BBB). Recent studies have demonstrated significant modulation of the BBB in a number of diseases and physiological states, including pain. This study expands on previous explorations of acute and chronic pain-induced effects on the function and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…Recently, we have begun to delineate specific biochemical mechanisms that enable peripheral pain/inflammation to "transmit" upstream signals and alter TJ protein expression and/or BBB permeability. For example, Brooks et al (5) administered diclofenac, a commonly prescribed nonsteroidal anti-inflammatory drug, to rats subjected to CIP and demonstrated that this therapeutic compound attenuated the increase in BBB permeability to sucrose observed in CIP animals (5). The results of this study and others (7) have clearly shown that cyclooxygenase activity is a critical regulator of BBB functional integrity.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Recently, we have begun to delineate specific biochemical mechanisms that enable peripheral pain/inflammation to "transmit" upstream signals and alter TJ protein expression and/or BBB permeability. For example, Brooks et al (5) administered diclofenac, a commonly prescribed nonsteroidal anti-inflammatory drug, to rats subjected to CIP and demonstrated that this therapeutic compound attenuated the increase in BBB permeability to sucrose observed in CIP animals (5). The results of this study and others (7) have clearly shown that cyclooxygenase activity is a critical regulator of BBB functional integrity.…”
Section: Discussionsupporting
confidence: 52%
“…Increased presence of 3-nitrotysine protein adducts is indicative of oxidative stress, which leads to disruption of TJ protein complexes. Specifically, occludin oligomeric assemblies are modulated (4), which then leads to increased paracellular permeability and enhanced access of the brain extracellular milieu to therapeutic agents such as codeine (5). Administration of SOD mimetics such as tempol prevents endothelial cell damage and protects the blood-brain barrier from pathological changes associated with pain/inflammation (i.e., increased permeability to circulating solutes and disruption of TJ protein complexes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that TNF-␣ treatment had differential effects on endothelia from the cerebrum and cerebellum because the barrier function was affected to a greater extent in the cerebellar than cerebral endothelium, and TNF-␣ treatment resulted in decreases in claudin-1, claudin-3, claudin-5, and occludin mRNA levels in the cerebellar endothelium (41). Brooks et al (5) showed that inflammatory pain is associated with regionally specific molecular and functional regulation of the blood-brain barrier. Hence, taken together with our findings, it appears that treatments that reinforce (29,39,44,45) or damage the barrier (5, 41) have differential effects on the barrier endothelium in different brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has shown, in vivo, modifications in functional BBB integrity and changes in CNS drug delivery induced by peripheral inflammatory pain (Huber et al, 2001;Hau et al, 2004;Brooks et al, 2006Brooks et al, , 2008Seelbach et al, 2007;Campos et al, 2008;Ronaldson et al, 2009). The critical link between inflammation in peripheral tissues and altered BBB permeability and/or transport may involve changes in serum cytokines such as transforming growth factor-␤ (TGF-␤).…”
Section: Introductionmentioning
confidence: 99%